Oil-Spill Bioremediation, Using a Commercial Biopreparation "MicroBak" and a Consortium of Plasmid-Bearing Strains "V&O" with Associated Plants - Filonov, Andrey; Ovchinnikova, Anastasia; Vetrova, Anna; Puntus, Irina; Nechaeva, Irina; Petrikov, Kirill; Vlasova, Elena; Akhmetov, Lenar; Shestopalov, Alexander; Zabelin, Vladimir; Boronin, Alexander (IntechOpen, 2012)
None